Holocene paleoclimate history of Fallen Leaf Lake, CA., from geochemistry and sedimentology of well-dated sediment cores. (1st January 2016) - Noble, Paula J.; Ball, G.Ian; Zimmerman, Susan H.; Maloney, Jillian; Smith, Shane B.; Kent, Graham; Adams, Kenneth D.; Karlin, Robert E.; Driscoll, Neal
Abstract: Millennial-scale shifts in aridity patterns have been documented during the Holocene in the western United States, yet the precise timing, severity, and regional extent of these shifts prompts further study. We present lake sediment core data from Fallen Leaf Lake, a subalpine system at the southern end of the Lake Tahoe basin for which 80% of the contemporary inflow is derived from snowpack delivered by Pacific frontal storm systems. A high quality age model has been constructed using 14 C ages on plant macrofossils, 210 Pb, and the Tsoyowata tephra datum (7.74–7.95 cal kyr BP). One core captures the transition from the Late Tioga-younger Dryas glaciolacustrine package to laminated opaline clay at 11.48 cal kyr BP. Early Holocene sedimentation rates are relatively high (∼1.9 mm/year) and cooler winter temperatures are inferred by the presence of pebbles interpreted to be transported out into the lake via shore ice. There is a geochemically distinct interval from ∼4.71 to 3.65 cal kyr BP that is interpreted as a late Holocene neopluvial, characterized by depleted δ 13 C and lower C:N that point to reduced runoff of terrigenous organic matter, increased winter precipitation, and increased algal productivity. The largest Holocene signal in the cores occurs at the end of the neopluvial, at 3.65 cal kyr BP, and marks a shift into a climate state with variable precipitation, yet is overall more arid than the neopluvial. This new climate state persists for ∼3 ka, until the Little Ice Age. Low sedimentation rates (0.5 mm/year), the homogeneous opaline sediment, and steadily increasing contributions of terrestrial vs. algal organic matter in these cores suggest that the lowstand state of Fallen Leaf Lake may have been the norm from 3.65 to 0.55 cal kyr BP, punctuated by short term high precipitation years or multi-year intervals capable of rapid short duration lake level rise. Fallen Leaf Lake is strongly influenced by changes in winter precipitation and temperature, manifested largely by the geochemical proxies, and highlights unique advantages of subalpine lakes in regional paleoclimate reconstructions. Highlights: Lake Tahoe basin climatic history reconciled with Fallen Leaf Lake sediment cores. Cores have an unusually high quality, macrofossil 14 C-derived age model. Transition out of last glacial interval in Tahoe Basin occurs at ∼11.5 cal kyr BP. Late Holocene neopluvial occurs from 4.17 to 3.65 cal kyr BP. Climate state shifts at 3.65 cal kyr BP to increased aridity punctuated with high precipitation events.